Clinical research progress of Traditional Chinese Medicine nursing of dry eye (干眼中医护理临床研究进展) - TAN Ronghui (谭容慧); LI Gonghui (李贡辉) (Association of Integrative Nursing, 2023)
Dry eye is one of the most common ophthalmic diseases besides refractive error, which has great influence on patients' daily life and work. In this paper, by reviewing the Traditional Chinese medicine nursing methods of dry eye in recent years, it is found that thunder moxibustion, traditional Chinese medicine fumigation and atomization, eye scraping, acupoint massage, Traditional Chinese medicine external application and auricle point sticking pressure are the Traditional Chinese Medicine nursing techniques commonly used in dry eye in clinical practice. This paper further pointed out that combined application of a variety of Traditional Chinese medicine nursing techniques and the application of integrated Traditional Chinese and western medicine nursing is expected to further improve the effect of dry eye nursing. (干眼是目前临床常见的眼科疾病之一, 给患者日常生活和工作造成巨大影响。本研究主要总结了雷火灸、中药熏蒸、雾化、眼部刮痧、穴位按摩、中药外敷和耳穴贴压等临床中较常应用于干眼的中医护理技术的应用现状, 旨在为今后中医护理在干眼疾病中的规范化应用提供参考。)